Case report: Characterizing of free-floating pigmented vitreous cyst using swept-source optical coherence tomography - Shi, Kexin; Yin, Qichuan; Huang, Yuxin; Zheng, Sifan; Wang, Yao; Shentu, Xingchao (Frontiers in Medicine, 2024)
Aim A free-floating vitreous cyst is a rare eye disease. This study aimed to find diagnostic imaging methods and imaging features for vitreous cysts. Methods This article presents a case report along with a literature review of published cases of vitreous cysts. The case report describes a highly myopic 60-year-old woman with a pigmented, free-floating vitreous cyst in her right eye. A search of the PubMed database using the keywords “vitreous cyst” was performed to identify other cases reported in the literature and to summarize the imaging methods used to diagnose and visualize vitreous cysts and the imaging features of vitreous cysts. Results A thorough ophthalmic examination was performed in the present case, including slit-lamp photography, B-scan ultrasound, broad line fundus imaging, spectral-domain optical coherence tomography (SD-OCT), and ultra-wide field SS-OCT. The literature review revealed the imaging methods used in previously reported cases of vitreous cysts in which ultra-wide field SS-OCT has the advantages of wide scanning depth and high imaging clarity. Conclusion SS-OCT has an advantage over SD-OCT in providing intuitive morphological characteristic images for the diagnosis of posterior vitreous cysts. The comprehensive assessment of multimodal imaging examinations, including SS-OCT, is of significant value for the diagnosis and differential diagnosis of vitreous cysts.